One-dimensional polymeric iodoplumbate hybrids with lanthanide complex cations: syntheses, crystal structures, and photoelectric and photocatalytic properties. (4th November 2020) - Chen, Niannian; Gao, Yan; Tian, Yiming; Wu, Bing; Jia, Dingxian; Zhao, Shengxian
Abstract : New iodoplumbate hybrids were prepared using lanthanide complexes as SDAs. They exhibit a high photocurrent response, current density and photocatalytic activity in the degradation of CV. Abstract : New iodoplumbate hybrids with lanthanide complexes [La(DMF)8 ]Pb3 I9 (1 ) and [Ln(DMF)8 ]Pb5 I13 (Ln = Sm (2 ), Gd (3 )) (DMF = N, N -dimethylformamide) were prepared using octakis complex cations [Ln(DMF)8 ] 3+ formed in situ as structure directing agents by volatilizing at room temperature. The polymeric 1-D [Pb3 I9 ] n 3 n − anion in compound 1 is constructed by PbI6 octahedral units via face-sharing featuring a waved chain structure, while the 1-D [Pb5 I13 ] n 3 n − anion in 2 and 3 is composed of PbI6 units via both edge-sharing and face-sharing. The compounds 1–3 show steep band gaps at 3.02, 2.61, and 2.57 eV, respectively, indicating potential semiconducting properties. They exhibit catalytic activities in the photodegradation of organic pollutants like crystal violet (CV) and methylene blue (MB). Compounds 2 and 3 are more effective than 1 in the photocatalytic degradation of CV, which are related to their intensity of the photocurrent response. The photocurrent response, cyclic voltammetry measurements and photocatalytic mechanism investigation for compound 2 show that ˙OH radical and h + hole are the main reactive species in the degradation experiment of CV.